Evaluation of In Vitro Antifungal Activity of Garlic, Thyme, Aloe Vera, and Cinnamon Essential Oils Against Candida Albicans, Aspergillus Flavus, Aspergillus Niger and Mucor Himalis - Mohammad Hosein Sadeghi Zali; Saber Yousefi; Amin Hashempour; Nazereh Hashempour; Saman Seyedgholizadeh (Islamic Azad University, 2016)
Introduction: Antifungal drugs have major limitations such as fungal resistance to classical drugs and treatment costs. It has been reported that antifungal activity of some essential oils as safe combinations. Thus, the present study was conducted to investigate the antifungal activity of garlic, thyme, aloe vera and cinnamon essential oils against Candida albicans, Aspergillus flavus, Aspergillus niger and Mucor himalis. Methods: Antibacterial activities of essential oils were evaluated by disk diffusion assay. The data were collected for 1, 3, 7 and 10 days. Results: Findings indicated that all essential oils showed similar antifungal activity against A. flavus, A. niger and M. himalis. Garlic essential oil was more efficient against C. albicans compared with other essential oils. Conclusion: The selected essential oils can efficiently show antifungal activity against A. flavus, A. niger and M. himalis, but garlic essential oil showed antifungal activity against the selected fungus Thus, garlic essential oil can be suggested as helper for common antifungal drugs.